Environmental Catastrophes and Their Consequences - Rajasekaran Ekambaram; Meenal Rajasekaran (Journal of Current Research and Studies, 2025)
The relationship between the environment and human health has undergone life changing transformations due to rapid industrialization, urbanization and technological advancements. These changes have significantly altered the natural world, leading to far-reaching consequences for human well-being. This article examines the critical environmental shifts—such as climate change, biodiversity loss, pollution and resource depletion—and their direct impacts on human health, including respiratory diseases, cardiovascular conditions, mental health and the emergence of zoonotic diseases. Drawing on recent experimental data and scientific references, the article argues that the escalating environmental degradation may necessitate radical solutions, including space colonization and the evolution of altered human life forms capable of adapting to extraterrestrial conditions. The discussion highlights the urgency of transitioning to sustainable practices, reducing reliance on fossil fuels and addressing environmental challenges to ensure long-term human survival. The article also explores the potential for technological innovations, such as artificial intelligence to mitigate environmental risks and pave the way for a resilient future beyond Earth.